ANALISIS PEMBELAJARAN TEMATIK PADA KURIKULUM 2013 DI SDN TANJUNGREJO 1 MALANG - Yuniasih, Nury; Ladamay, Iskandar; Wahyuningtyas, Dyah Tri (Mimbar Sekolah Dasar, 2014)
This study aims to describe the implementation of thematic learning in SDN Tanjungrejo 1 Malang. The subjects were teachers and students of class I and IV SDN Tanjungrejo 1 Malang. The research approach used is qualitative research case study according to the research focus. Data collection techniques used in this study include: in-depth interviews, observation, and documentation. The results showed that the implementation of thematic learning in SDN Tanjungrejo 1 Malang is in accordance with the curriculum in 2013, but there are still some obstacles include: the ability of teachers to manage large classes and students who have not mastered basic skills. It can be concluded that the implementation of thematic learning class I and IV in SDN Tanjungrejo 1 Malang has been accomplished in accordance with the curriculum in 2013, but still requires the right strategy in order to be done well. Keywords: thematic learning, curriculum 2013.